Real-world evidence for coverage decisions: opportunities and challenges. (9th November 2018) - Hampson, Grace; Towse, Adrian; Dreitlein, William B; Henshall, Chris; Pearson, Steven D
Aim: To explore current uses of real-world evidence (RWE) in the US healthcare system, summarize key concerns and highlight various opportunities that could be realized through best use of RWE.Materials & methods: Information was gathered via a literature review and interviews to generate a background paper for the 2017 Institute for Clinical and Economic Review Policy Summit meeting.Results: RWE is currently being utilized in drug development decisions, regulatory approval decisions, post-approval monitoring, payer coverage decisions (initial decisions and reassessments) and for outcomes-based contracting. Solutions to key challenges and opportunities for future development are presented.Conclusion: Exciting opportunities for the use of RWE exist, yet important reservations remain. Solutions are within reach if effective partnerships between stakeholders can be nurtured.